A pedagogical framework of cross-cultural online collaborative projects in English as Foreign Language (EFL) classrooms - Yunchai Chen; Hsueh-Hua Chuang; Aurora Lacaste (Intelektual Pustaka Media Utama, 2021)
Many researchers have focused on online collaborative learning, cross-cultural communication, project-based learning, digital literacy, and digital storytelling but there is no pedagogical framework that incorporates these elements for English as Foreign Language (EFL) teaching. This study based on the qualitative design established a pedagogical framework from three different types of cross-cultural collaborative projects with the collected data including students’ artifacts and project structures. We have found that the pedagogical framework proposed here serves as a guide to facilitate different types of cross-cultural projects in their classrooms. The multiple cases of cross-cultural online collaborative projects in an EFL class were taught according to the theories of project-based learning and content language integrated learning alike, proved to follow this pedagogical framework. Implementation is also described to give more details on how the projects were conducted. In the end, opportunities and challenges are provided for future implementation of online collaborative EFL projects.